2021
DOI: 10.1186/s13054-021-03864-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for extubation failure in COVID-19 patients using a machine learning approach

Abstract: Introduction Determining the optimal timing for extubation can be challenging in the intensive care. In this study, we aim to identify predictors for extubation failure in critically ill patients with COVID-19. Methods We used highly granular data from 3464 adult critically ill COVID patients in the multicenter Dutch Data Warehouse, including demographics, clinical observations, medications, fluid balance, laboratory values, vital signs, and data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
1
17
1
Order By: Relevance
“…On the other hand, several studies have shown lately that patients with COVID-19 infection and neurological comorbidities and illnesses such as history of prior strokes and cerebrovascular events, are more likely to be intubated, as the neurological status of these patients is considered to be a strong predictor of adverse health effects [25,26]. Moreover, Glasgow coma scale, responsible for evaluating the degree of consciousness and brain damage in patients with COVID-19 infection, is considered to be a predictor for intubation [27]. A deviation in the Glasgow coma scale score in patients with COVID-19 infection was significantly correlated to death [28].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies have shown lately that patients with COVID-19 infection and neurological comorbidities and illnesses such as history of prior strokes and cerebrovascular events, are more likely to be intubated, as the neurological status of these patients is considered to be a strong predictor of adverse health effects [25,26]. Moreover, Glasgow coma scale, responsible for evaluating the degree of consciousness and brain damage in patients with COVID-19 infection, is considered to be a predictor for intubation [27]. A deviation in the Glasgow coma scale score in patients with COVID-19 infection was significantly correlated to death [28].…”
Section: Discussionmentioning
confidence: 99%
“…FiO 2 was set as 0.4, and flow was set at 60 L/min to gain the maximum benefit from high-flow oxygen device [15,19]. To minimize the effects of oxygenation on the weaning failure, FiO 2 level was set at 0.4 in both groups [1,17,20]. In both groups, SBT was performed for 30-60 min (or less in case of clinical intolerance).…”
Section: Interventionsmentioning
confidence: 99%
“…With great interest, I read the article by Fleuren et al on determining the predictors for extubation failure in COVID-19 patients [ 1 ]. The authors have methodically utilised the machine learning models to identify the potential parameters that would predict the extubation failure in critically ill COVID-19 patients.…”
Section: Dear Editormentioning
confidence: 99%